Confronting Therapeutic Failure: A Conversation Guide. (22nd June 2015) - Morgans, Alicia K.; Schapira, Lidia
Abstract : We reflect on the impact of bad news on both clinician and patient in the setting of cancer treatment failure. We review the classic six‐step SPIKES (setting, perception, invitation for information, knowledge, empathy, summarize and strategize) protocol for giving bad news that has been widely adopted since it was first published in this journal in 2005. The goal of such a conversation guide is to describe both the process and the tasks that constitute vital steps for clinicians and to comment on the emotional impact of the conversation on the clinician. Confronting therapeutic failure is the hardest task for oncologists. We offer practical tips derived from a thorough review of the evidence and our clinical experience. Implications for Practice: Discussing the failure of anticancer therapy remains a very difficult conversation for oncologists and their patients. In this article, the process of confronting this failure is broken down into various components,  and practical tips are provided for clinicians following a classic protocol for breaking bad news. Also addressed are the emotions of the oncologist and the reasons why these conversations are typically so hard. These insights are based on solid research intended to deepen the therapeutic connection between physician and patient. Abstract : The classic six‐step SPIKES (setting, perception, invitation for information, knowledge, empathy, summarize or strategize) protocol for giving bad news is reviewed. Practical tips derived from a thorough review of the evidence and our clinical experience are offered.